The Affinity of Local Political Branding Toward The Distinction of Constituent Taste in NTT - Mikhael Rajamuda Bataona; Donna Isra Silaban; Yoseph Riang; Emanuel Sowe Leuape; Benjamin Laurentino Vaz (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
This study examines the relationship between candidates’ branding politic and the political preferences (selera) of voter groups during the 2024 Nusa Tenggara Timur (NTT) gubernatorial election. The research is grounded in the strong influence of local political culture in shaping political orientation, both among elites and the general public. The main objectives of this study are: (1) to identify the distingsi of political selera among the public based on their ideal leadership qualifications, and (2) to analyze the alignment between candidates’ branding politik and those political selera. This research employs a critical approach with a single-case study design. The findings reveal three categories of voter selera politik: Legitimate Taste (upper class), Middle-Brow Taste (middle class), and Popular Taste (lower class). The three gubernatorial candidate pairs presented distinct branding: Lema–Natalia portrayed a millennial-opposition figure; Lena–Asadoma emphasized political networks and accommodative communication; Kamlasi–Garu highlighted local Timorese identity. All candidates capitalized on symbolic capital to reach middle- and lower-class voters. The study concludes that political preference in NTT is not entirely shaped by rationality, but rather by culturally and symbolically embedded selera. This research underscores that the hegemony of local political culture remains highly dominant in the dynamics of political contestation and strategy in NTT